Heart transplantation from older donors - V. N. Poptsov; E. A. Spirina; N. N. Koloskova; S. A. Masyutin; S. G. Ukhrenkov; A. A. Dogonasheva (Вестник трансплантологии и искусственных органов, 2017)
In the current situation of the shortage of suitable donor organs, heart transplantation from older donors is one of the ways to increase the performance of more heart transplants, particularly, in patients with urgent need of transplantation. While planning a heart transplantation from older donor one should consider increased risk of early cardiac allograft dysfunction, preexisting coronary artery disease, accelerated transplant vasculopathy which may adversely affect early and long-term survival of recipients. Subject to careful selection of donor–recipient pairs, effective prevention and treatment of early cardiac allograft dysfunction, pre-existing atherosclerosis and transplant vasculopathy the early and long-term survival of heart transplant recipients from older donors is comparable to heart transplantation from young donors.